The Relationship Between Low Birth Weight and Survival Rate in Premature Babies - Pamarga Priyambodo; Hermanto Tri Joewono; Risa Etika (Humanistic Network for Science and Technology (HNST), 2021)
Preterm birth is a birth that occurs before 37 weeks of gestation where low birth weight is often found at the same time. This combination of low birth weight and preterm has the potential to cause morbidity and mortality. The aim of this study was to study the relationship between low birth weight and survival rate in preterm infants. The research method used is systematic review approach obtained from 7 research studies in various countries and fulfills the inclusion and exclusion criteria. The variables studied were infant birth weight and survival rate using instruments in the form of studies that have been published on Google Scholar, PubMed, and Science Direct. The article search method uses the characteristics of PICO (Population, Intervention, Comparison, Outcome), then the data in the form of articles that have been collected is managed using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) method. From the 7 articles that were reviewed, it was found that the lower limit of the survival rate in the ELBW category studied was 30.8%, 20.5%, 34.8%, 7%, 69.6%, 58.5%, and 59%. Then at the upper limit in the VLBW and LBW categories, numbers such as 91.8%, 95.6%, 84.8%, 92%, 97.9%, 95%, and 98.1% are obtained. There are consistent results, namely an increase in the survival rate with increasing birth weight, which shows a significant relationship between the two. Keywords: preterm; survival rate; low birth weight